INOVASI DAN PENGEMBANGAN PRODUK UKM HANDIKRAF UNTUK PASAR PARIWISATA DI BALI - Abdillah, Yusri (Profit: Jurnal Adminsitrasi Bisnis, 2016)
Tourism is a sector that has a comprehensive multiplayer effect and provide opportunities for a variety of industries to develop through service to the needs of tourists. This study discusses the role of tourism to the development of the handicraft industry as a supplier of souvenir at the tourist market. More specifically the study was conducted to examine the process of innovation in product development of small businesses producing crafts in Malang which sells its products to market tourism in Bali. The results showed that innovation in product development and behavior is dominated by the design desired by intermediaries compared to designs offered by the company. This indicates that the intermediaries had more accurate information about the preferences of the market compared with craft souvenir producers. Thus, the manufacturers producing handicrafts for souvenirs is more to position themselves as "peasant" in order to ensure the economic viability of production and yet have sufficient orientation towards market developments directly.